2002
DOI: 10.1038/sj.pcan.4500573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pulmonary metastases in stage D2 prostate cancer patients

Abstract: Several prognostic factors such as the extent of bone metastases (EOD) in advanced prostate cancer (PCa) have been reported. Metastasis of the lung is rarely a significant clinical factor in the management of prostate cancer. The present study evaluates the clinical significance of lung metastases. We retrospectively reviewed the PCa database to identify patients with pulmonary metastases at initial diagnosis. The medical records of the patients were examined with respect to age, histologic grade, EOD score, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The significant difference in the percentages of patients with visceral metastasis only and those with bone metastasis suggests that these conditions have distinct biology. This is further supported by the observation that bone metastasis is an important prognostic factor in prostate cancer [10,20–22], while pulmonary metastasis has no significant effect on disease outcome [23].…”
Section: Discussionmentioning
confidence: 71%
“…The significant difference in the percentages of patients with visceral metastasis only and those with bone metastasis suggests that these conditions have distinct biology. This is further supported by the observation that bone metastasis is an important prognostic factor in prostate cancer [10,20–22], while pulmonary metastasis has no significant effect on disease outcome [23].…”
Section: Discussionmentioning
confidence: 71%
“…These distal lesions are often refractory to conventional therapies and continue to grow, resulting in high mortality associated with metastatic PC (56)(57)(58). Present results have shown that endogenous expression of hCT may be an important factor in oncogenicity of PC cells, and have identified that PKA is an important mediator of oncogenic actions of hCT in PC-3M and LNCaP cells.…”
Section: Discussionmentioning
confidence: 79%
“…[58][59][60][61] These distal lesions are often refractory to conventional therapies and continue to grow, resulting in high mortality associated with metastatic prostate cancer. [62][63][64] Previous studies from our laboratory have shown that the expression of CT and its receptor is upregulated with the progression of prostate carcinoma. 9 The present results that CT causes a marked increase in their invasiveness by activating PKA-mediated intracellular mechanisms suggest the role for CT and PKA in increased tumorigenicity and invasiveness of advanced prostate tumors.…”
Section: Discussionmentioning
confidence: 99%